2003
DOI: 10.1080/13651820310001379
|View full text |Cite
|
Sign up to set email alerts
|

Mini‐cholecystectomy: a personal series in acute and chronic cholecystitis

Abstract: MC is an effective surgical procedure for an inflamed gallbladder regardless of the degree and type of inflammation. Patients with chronic cholecystitis recover more quickly and have a shorter hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…31,32 After the introduction of laparoscopy during the 80s and in 1985, LC has overtaken open surgery for cholelithiasis as a technological revolution even though smaller incision open cholecystectomy, introduced in early 1982 had shown successful outcome with a shorter convalescence. 4,5,33 Open cholecystectomies have stayed and are performed with a less cost, the need of equipment, and training. [1][2][3][4][5][6][7] comparing conventional OC and LC continue to unfairly One patient had a subtotal cholecystectomy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…31,32 After the introduction of laparoscopy during the 80s and in 1985, LC has overtaken open surgery for cholelithiasis as a technological revolution even though smaller incision open cholecystectomy, introduced in early 1982 had shown successful outcome with a shorter convalescence. 4,5,33 Open cholecystectomies have stayed and are performed with a less cost, the need of equipment, and training. [1][2][3][4][5][6][7] comparing conventional OC and LC continue to unfairly One patient had a subtotal cholecystectomy.…”
Section: Resultsmentioning
confidence: 99%
“…4,5,33 Open cholecystectomies have stayed and are performed with a less cost, the need of equipment, and training. [1][2][3][4][5][6][7] comparing conventional OC and LC continue to unfairly One patient had a subtotal cholecystectomy. Separation of adhered omentum revealed a thick wall friable GB with necrosis at the fundus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 2,000 cases of Mini-Cholecystectomy (MC) have been reported worldwide without any deaths or major common bile duct injuries since the first report in 1982. (1)(2)(3)5,(7)(8)(9)(10)(11)(12) Although three randomized controlled trials showed better results for Local anesthesia (LC)…”
Section: Discussionmentioning
confidence: 99%
“…(5)(6)(7)(8) More recently, Mini-Cholecystectomy (MC) has been shown to be an effective surgical procedure for an inflamed gallbladder regardless of the degree and type of inflammation. (9) Both Mini-Cholecystectomy (MC) and laparoscopic Cholecystectomy(LC) are usually performed under general anesthesia. However, it is likely that in suitable patients or in those who are unwilling to have general anesthesia or have severe contraindications to narcosis, the gallbladder can be excised under local anesthesia through a very small incision.…”
Section: Introductionmentioning
confidence: 99%